Monitoring Adherence to Asthma Inhalers Using the InspirerMundi App: Analysis of Real-World, Medium-Term Feasibility Studies - Jácome, Cristina; Almeida, Rute; Pereira, Ana Margarida; Amaral, Rita; Vieira-Marques, Pedro; Mendes, Sandra; Alves-Correia, Magna; Ferreira, José Alberto; Lopes, Inês; Gomes, Joana; Araújo, Luís; Couto, Mariana; et al. (Frontiers in Medical Technology, 2021)
Poor medication adherence is a major challenge in asthma and objective assessment of inhaler adherence is needed. InspirerMundi app aims to monitor inhaler adherence while turning into a positive experience through gamification and social support. We assessed the medium-term feasibility of the InspirerMundi app to monitor inhaler adherence in real-world patients with persistent asthma (treated with daily inhaled medication). In addition, we attempted to identify the patients’ characteristics related to a higher app use. Two real-world multicenter observational studies, with one initial face-to-face visit and a 4-month telephone interview, were conducted in 29 secondary care centers from Portugal. During an initial face-to-face visit, patients were invited to use the app daily to register their asthma medication intakes. A scheduled intake was considered taken when patients took a photo of the medication (inhaler, blister, or others) using the image-based medication detection tool. Medication adherence was calculated as the number of doses taken as a percentage of the number scheduled. Interacting with the app ≥30 days was used as cut-off for a higher app use. A total of 114 patients (median 20[P25-P75 16-36] years, 62% adults) were invited, 107(94%) installed the app and 83 (73%) completed the 4-month interview. Patients interacted with the app for a median of 18[3-45] days, translated on a median use rate of 15[3-38]%. Median inhaler adherence assessed through the app was 34[4-73] % when considering all scheduled inhalations for the study period. Inhaler adherence assessed was not significantly correlated with self-reported estimates. Median adherence for oral and other medication was 41[6-83]% and 43[3-73]%, respectively. Patients with higher app use were slightly older (p=0.012), more frequently taking medication for other health conditions (p=0.040) and more frequently prescribed LAMA (long-acting muscarinic antagonists, p=0.024). After 4 months, CARAT scores improved (p<0.001), but no differences between patients interacting with the app for 30 days or less were seen. The InspirerMundi app was feasible to monitor inhaler adherence in patients with persistent asthma. Persistence of use of this mHealth technology varies widely. A better understanding of characteristics related with higher app use is still needed before effectiveness studies are undertaken.